A Novel Sustainable Semiconductor/Metal-organic Framework Coated Electret Filter for Simultaneous Removal of PM2.5 and VOCs - Yu Zhang; Zan Zhu; Wei-Ning Wang; Sheng-Chieh Chen (Aerosol and Air Quality Research)
Abstract A MIL-125-NH2 metal-organic framework (MOF) coated electret filter, named E-MOFilter, was previously developed to simultaneously remove PM2.5 (particulate matter less than 2.5 µm in aerodynamic diameter) and volatile organic compounds (VOCs, e.g., toluene). This E-MOFilter captures toluene primarily through physical adsorption, however, degradation of the adsorbed VOCs is desired for increasing the service life of the filter. In this study, photocatalytic nanosheets Bi2WO6/BiOCl (p-BWO) were synthesized, grafted on the MIL-125-NH2 to be p-BWO@MIL, and then coated to the electret filter to form a new filter named PE-MOFilter. The physical characterizations, including size, morphology, crystal structure, optical properties, and surface area for the semiconductor p-BWO nanosheets, p-BWO@MIL and PE-MOFilter were first examined to find out the optimal p-BWO to MIL ratio and coating wt% of p-BWO@MIL particles on the electret filter. Results demonstrated that the p-BWO nanosheets were successfully coated on the surface of MIL and the p-BWO@MIL retained the surface area and micropore volume of the MIL-125-NH2. The capability of the PE-MOFilter on adsorption and degradation of VOCs and the removal efficiency of PM2.5 was examined. The results showed that this novel PE-MOFilter not only captured but also effectively photodegraded VOC pollutants via the synergistic action of adsorption and photocatalytic oxidation (PCO). The photodegradation efficiency was found to be as high as 68.7% and it depended on the ratio of p-BWO to MIL. The PM2.5 removal efficiency also demonstrated that the coating of p-BWO@MIL particles had a negligible influence on the degradation of fiber charge. This research sheds light on the development of semiconductor@MOF coated electret media to simultaneously remove particulate and gaseous pollutants to improve indoor air quality with low energy consumption.